Genome-Wide Profiling of Plutella xylostella Immunity-Related miRNAs after Isaria fumosorosea Infection - Xu, Jin; Xu, Xiaoxia; Li, Shuzhong; Wang, Shuang; Xu, Xiaojing; Zhou, Xianqiang; Yu, Jialin; Yu, Xiaoqiang; Shakeel, Muhammad; Jin, Fengliang (Frontiers in Physiology, 2017)
The development of resistance by Plutella xylostella to almost all insecticides is of significant concern all over the world. Entomopathogenic fungi such as Isaria fumosorosea have been used as an alternative to insecticides. However, the knowledge of miRNA-regulated reactions against entomopathogenic fungi is still in its infant stage. In the present study, P. xylostella was challenged with I. fumosorosea at four different time points (12 h, 18 h, 24 h, and 36 h) including a control, to build miRNA libraries by Illumina sequencing. The results of differential expression analysis exhibited that 23 miRNAs were differentially expressed, compared to control, in all treatments. It is worth mentioning, of these, some conserved miRNAs such as miR-2, miR-9a, miR-745, miR-7b, and miR-2767, known to play critical roles in host-pathogen interaction, were also identified. Furthermore, differentially expressed miRNAs were validated by RT-qPCR. Our results provide an essential information for further functional studies of the interaction between I. fumosorosea and P. xylostella at the post-transcriptional level.